(untitled) (ETIMA, 2021)
Abstract Lighting systems pass through big change in terms of light source recently. LED replace discharge lamp and this change represent change of electrical parameters and influence to installations. Lighting systems with discharge lamp use inductive ballasts with choke and starter or electronic ballasts. Lamps with LED use drivers which are switching sources. The drives include rectifier, high frequency oscillator, transformer and capacitors. Typically, rectifier has impact to distortion of luminaire current and capacitor has impact to inrush current. Over the last years, problem increases with inrush current. Public lighting networks reconstruct with LED luminaires. Often increase inrush current and circuit-breaker must be changed for stronger. This change cause increasing of payment for energy distribution and sometime is necessary change installation. Aim of this paper is describe difference between luminaires from point of view inrush current. Size and duration of inrush current depends on construction of driver and on phase of supply voltage. In paper are analyzed amplitudes, durations and behavior of electrical parameters various LED luminaires. Key words LED, lamp, driver, inrush current